2015
DOI: 10.5539/ijsp.v4n2p55
|View full text |Cite
|
Sign up to set email alerts
|

Quantile Plots of the Prediction Variance for Partially Replicated Central Composite Design

Abstract: Sometimes, it is not feasible to fully replicate the experimental units. When this happen, there is need for optimal replication of the experimental units to avoid bias. The prediction variance of two variations of the partially replicated central composite design (replicated cube plus one star and one cube plus replicated star) are compared using the quantile plots. These plots provide information about the prediction variance distribution on a sphere for comprehensive evaluation of the quality of the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They concluded that the replicated-star options always give smaller G-and I-optimal values than the corresponding replicated-cube options with equal number of replications. In [9] the author(s) used quantile plots to compare the prediction variance of partially replicated face center cube and rotatable central composite design. They concluded that the performance of the factorial with replicated axial points in both design is preferred to the replicated factorial portion with one axial portion.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the replicated-star options always give smaller G-and I-optimal values than the corresponding replicated-cube options with equal number of replications. In [9] the author(s) used quantile plots to compare the prediction variance of partially replicated face center cube and rotatable central composite design. They concluded that the performance of the factorial with replicated axial points in both design is preferred to the replicated factorial portion with one axial portion.…”
Section: Introductionmentioning
confidence: 99%